Evaluation of the Effectiveness of Organic Matter Biodegradation by a Bacterial Consortium in Vannamei Shrimp Farming Wastewater - A. Fahmi Nada; Surya Rachman Susilowati; Asus Maizar Suryanto Hertika; Maftuch (Postgraduate, University of Mataram, 2025)
This study evaluated the effectiveness of a bacterial consortium for biodegrading organic waste in vaname shrimp (Litopenaeus vannamei) farming wastewater. A completely randomized design with four treatments (1, 2, and 3 ppm, plus a control) and three replicates per treatment was used. The consortium, consisting of Lactobacillus casei, Bacillus subtilis, Bifidobacterium sp., Nitrosomonas sp., and Nitrobacter sp., was cultured in a medium containing molasses, rice bran, brown sugar, and whole milk. Over a 5-day incubation period, key parameters (TOM, BOD, ammonia, nitrite, nitrate, and bacterial viability) were measured. The 3 ppm treatment achieved the highest reductions TOM by 61.4%, BOD by 69.57%, ammonia by 68.92%, nitrite by 67.59%, and nitrate by 62.02% with bacterial viability increasing by 165% compared to the control. These results demonstrate that the optimal dose significantly enhances biodegradation under conditions of 24.3–28.9°C, pH 7.8–8.5, and DO 3.5–6.8 mg/L. In conclusion, applying the bacterial consortium at 3 ppm offers an eco-friendly and effective strategy to improve water quality in intensive shrimp aquaculture, supporting national food security and Blue Economy initiatives.